Proposta de um plano de manutenção dos veículos automoto-res do transporte escolar da prefeitura municipal de Olho D’água do Borges - Sales, Kairo Medeiros (Universidade Federal Rural do Semi-Árido, 2019)
The maintenance in the companies is of fundamental importance to keep the company with its maximum production and the minimum of losses by unscheduled stops, with that, the ma-nourishment becomes a fundamental pillar for the company to have competitive results. Un-fortunately, the public sector still suffers from seeing that maintenance is an expense rather than an investment. This work aimed to make a survey of the critical points of the pubic School transport of the municipality of Olho D'água do Borges, doing a bibliographic study, later a survey was made of the failures of these transports in a given period, seeing that they were only maintenance corrective, without the existence of any type of planning for its maintenance. The TPM philosophy was chosen for the implementation, since it involves all of the company in the maintenance, so, if implemented well, it will increase the efficiency of the services provided to the population. At the end of this work, all the vehicle failures were pre-sented within a year and a Check List was presented, which must be completed by the drivers, and a maintenance plan was drawn up to be followed up in the next maintenance.
Monografia
Keywords: Manutenção total produtiva; Plano de manutenção; Transporte escolar; ENGENHARIAS::ENGENHARIA MECANICA